Psevdociste trebušne slinavke - Pleskovič, Alojz (Medicinski razgledi, 2000)
Pancreatic pseudocysts, which develop as a complication of acute and chronic inflammation and pancreatic trauma, are a collection of pancreatic secretory products surrounded by a fibrous sac. It is important to differentiate these pseudocysts from acute fluid collections and other benign and malignant cysticlesions of the pancreas. Patients with a history of pancreatitis and developing pseudocyst present with a variety of signs and symptoms. Pseudocysts can cause a number of complications, the most dangerous one being acute haemorrhage into the pseudocyst, which requires immediate surgical intervention. Ultrasonography and computed tomography are essential to an accurate diagnosis of pancreatic pseudocysts. Patients with stable pseudocystsand no symptoms or complications are well taken care of by regular follow-ups. Surgical treatment with internal drainage is the therapy of choicein well-developed uncomplicated pseudocysts. Standard and alternative therapeutic approaches are described.
Keywords: Pancreatic pseudocyst; trebušna slinavka; psevdociste; Diagnosis; zdravljenje; Complications; Therapy; Diagnosis, differential